A munkaügyi alternatív vitafeloldó módszerek a bírósághoz fordulás alapjogának fényében - Nádházy, Zsolt (Debreceni Jogi Műhely, 2005)
Thanking to the fact that numerous European countries have become more democratized, and to the practical experience based on common law legal system, from the middle of the XXth century some of the continental legal systems have begun to apply alternative procedures for solving disputes between parties, such as facilitation, arbitration or mediation. We can stress two important common features of these solutions. Firstly, if parties apply these ways, they can avoid the traditional judicial way (or, if the result of the chosen method is not satisfactory, these ways can be considered as the preliminary step before the judicial way). Secondly, these procedures have appeared firstly in labour law. As we emphasized, applying these solutions parties try to avoid the judicial way, for this reason in this study we try to introduce the relationship between these methods and the basic right to turn a (traditional) court. Expert’s opinions in connection with these processes are very different, we introduce only the two farthest standpoint: on the one hand these ways can speed up the procedure between parties, and can increase the efficiency of it, and parties can agree with each other by amicable way. On the other hand, applying these ways some of the basic rights (for example the principle of independence of courts and the right of fair trial or the principle of contradictory) will be decreased. In this study we try to examine the problem determined in the title, on the basis of the rules of the Convention for the Protection of Human Rights and Fundamental Freedoms, and the Constitution of Hungary. But, we have to examine not only the right of fair trial and turning to a (traditional) court, but the monopoly of courts in connection with solving legal disputes (as constitutional principle) in details. We utilize the orders of the Hungarian Constitutional Court as well as the theological and practical experience of these procedures. We have to emphasize that from the different alternative dispute-solving mechanisms we examine not all of the models, but only the model of New York, because only the procedures follow these model are relevant for us in this study.